Comparación agronómica de híbridos de maíz para ensilaje en las condiciones agroecológicas en la zona sur del Paraguay (Journal on studies and research of academic knowledge, 2014)
The research was conducted to generate local information regarding the agronomic and productive performance of different hybrids of corn silage was performed at the Center for Livestock Research Itapúa, the experimental design was randomized complete block with three replications hybrids evaluated were 10 different companies that are represented in the pay zone, the variables evaluated were plant height and yield of green matter, analysis of variance significant difference was detected for the variable yield of green matter. Thus obtained it can be concluded that maize hybrids were influenced by the agro ecological environment is a factor that has an impact on the genetic origin of the hybrids.
Keywords: hybrid corn; agronomic performance; agro-ecological environment